The Effect of Social Supports on Self-Efficacy among Female Students at Islamic Universities - Paulina, Melisa; Rusli, Ris'an; al-Kaf, Idrus; S. Bintang, Rahmat; Qadriyah, Siti Rahmi; Lintina, Shovia; Masita Adnan, Eva; Mistarija, Mistarija; Bukhari, Bukhari; Trilia, Trilia; Permana, Dede; Fajri Busti, Muharramainil (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Female students face additional stress and difficulties in adjusting to higher education which negatively impacts academic performance. Due to the dual roles, academic requirements and housekeeping activities, that are played by female students, social support is needed in forming self-efficacy in female students to achieve learning goals. This study aimed to examine the relationship between family support, friend supports, and support from significant others among female students at Islamic universities. In this research, a quantitative method was used with 286 Islamic female students as the subjects, selected using non-probability sampling technique. In this study, the researchers used conformational factor analysis (CFA) using Lisrel 8.8 to test the validity of the measuring instrument. To analyze descriptive statistics, SPSS 23 software was used. The result of this research was that there was a significant and positive influence between social support on self-efficacy of female students of 0.109 or 10.9 %, while the remaining 80.1 % was influenced by other variables outside the research. Based on the analysis of the influence of each independent variable on the dependent variable in this research, there were two dimensions whose regression coefficient values were significant, namely the dimension of family support and significant other and dimension of social support that was not significant, namely the dimension of friend supports.